2004
DOI: 10.1029/2003jd004248
|View full text |Cite
|
Sign up to set email alerts
|

Transport of smoke from Canadian forest fires to the surface near Washington, D.C.: Injection height, entrainment, and optical properties

Abstract: [1] Smoke and pollutants from Canadian forest fires are sometimes transported over the United States at low altitudes behind advancing cold fronts. An unusual event occurred in July 2002 in which smoke from fires in Quebec was observed by satellite, lidar, and aircraft to arrive over the Washington, D.C., area at high altitudes. This elevated smoke plume subsequently mixed to the surface as it was entrained into the turbulent planetary boundary layer and had adverse effects on the surface air quality over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
199
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(209 citation statements)
references
References 39 publications
6
199
0
Order By: Relevance
“…Similar to the study presented here, Canadian wildfires have increased O 3 concentrations in Houston, TX (Morris et al, 2006), and as far away as Europe (Spichtinger et al, 2001). Evidence of Canadian wildfire smoke and biomass burning affecting the MA's particulate matter (PM) air quality was also previously reported (Adam et al, 2004;Colarco et al, 2004;Sapkota et al, 2005), but wildfire smoke has also been recognized in high-O 3 events on the East Coast (Fiore et al, 2014). DeBell et al (2004) presented a chemical characterization of the July 2002 Quebec wildfire smoke plume and its impact on atmospheric chemistry in the northeastern United States.…”
Section: Introductionsupporting
confidence: 82%
“…Similar to the study presented here, Canadian wildfires have increased O 3 concentrations in Houston, TX (Morris et al, 2006), and as far away as Europe (Spichtinger et al, 2001). Evidence of Canadian wildfire smoke and biomass burning affecting the MA's particulate matter (PM) air quality was also previously reported (Adam et al, 2004;Colarco et al, 2004;Sapkota et al, 2005), but wildfire smoke has also been recognized in high-O 3 events on the East Coast (Fiore et al, 2014). DeBell et al (2004) presented a chemical characterization of the July 2002 Quebec wildfire smoke plume and its impact on atmospheric chemistry in the northeastern United States.…”
Section: Introductionsupporting
confidence: 82%
“…Other studies provided good agreement of model simulations with observations for an emission release between the surface and the planetary boundary layer (PBL) height as well as a fixed height of 1.2 km (Wang et al, 2006;Matichuk et al, 2007). While Jian and Fu (2014) found a large sensitivity of BC concentrations on the emission heights, Colarco (2004) demonstrated that the differences between a near-surface emission release and a release between 2 and 6 km are small for convective atmospheric conditions. Chen et al (2009) used the GEOS-CHEM model with Global Fire Emission Data Base 2 (GFED2) emissions to simulate the smoke transport from North American forest fires.…”
Section: A Veira Et Al: Impact On Transport Black Carbon Concentramentioning
confidence: 72%
“…Aloft aerosol plumes from both forest-fires and dust storms events are often transported over long distance, affecting both climate radiation and air quality on regional/continental scales [1,2]. They often result in significant contribution to the column aerosol optical depths (AOD) which can bias the estimate of PM2.5 from the satellite column observation [3,4].…”
Section: Introductionmentioning
confidence: 99%